The Application of Active Knowledge Sharing Method in Microteaching Courses to Improve Communication Skills - Nurul Salis Alamin; Nurul Azizah; Mutiara Dewi (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the effectiveness of the Active Knowledge Sharing strategy in improving the communication skills of pre-service teachers in Microteaching courses. Microteaching provides a practical bridge between theory and classroom practice, while 21st-century teaching requires strong interpersonal and verbal competencies. The Active Knowledge Sharing approach, which emphasizes collaboration, discussion, and knowledge exchange, encourages active participation, reflective thinking, and effective communication. This study employed the Kemmis and Taggart action research model across two cycles, revealing significant improvement in students’ communication skills, with the mean score rising from 2.91 (Good) in Cycle I to 3.70 (Excellent) in Cycle II. The most notable progress was observed in the “Using Language Effectively” aspect, indicating enhanced confidence, clarity, and active engagement during microteaching sessions. These results suggest that Active Knowledge Sharing is an effective pedagogical method for developing communication competence and can contribute to improving the quality of teacher training programs.